2006
DOI: 10.3846/16486897.2006.9636881
|View full text |Cite
|
Sign up to set email alerts
|

Change Cyclicity of Volumetric Activity of Radionuclide 137cs in Coastal Waters of the Baltic Sea and Its Possible Reasons

Abstract: Monitoring of the volumetric activity of a radionuclide 137Cs in the coastal waters of the Baltic Sea was carried out near the settlement of Juodkrante in the summer – autumn of 2004. Three measurement stages of the VA of this radionuclide were carried out and hydrometeorological situations were considered simultaneously. 137Cs VA change cyclicity was found out near the seacoast. Extreme data for the whole period of observation were 48 and 94 Bq/m3. Maximal values exceeded minimal data approximately two times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The detailed measurements of 137 Cs VA in the coastal waters of the SEPBS were carried out in 2004. The obtained results showed that the measurement values exceeded calculated data two times or more [20]. However, a satisfactory coincidence of measured and calculated results in the summer and autumn of 2005 was observed.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…The detailed measurements of 137 Cs VA in the coastal waters of the SEPBS were carried out in 2004. The obtained results showed that the measurement values exceeded calculated data two times or more [20]. However, a satisfactory coincidence of measured and calculated results in the summer and autumn of 2005 was observed.…”
Section: Introductionmentioning
confidence: 58%
“…The highest values are registered in 2004, when the greatest instability of absolute values of 137 Cs VA was observed [20]. The curves presented in Fig 2 define a possible tendency of changes in 137 Cs VA in coastal waters of the Baltic Sea.…”
Section: Measurement Results and Their Analysismentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, in 2004 the extreme values of 137 Cs VA were 94 and 49 Bq/m 3 [ 10 ] and 90 Sr VA were 17 and 7 Bq/m 3 [ 11 ]. They indicate major changes in the absolute values of the radionuclide VA.…”
Section: Introductionmentioning
confidence: 99%